Landasan Pembentukan Karakter dalam Kitab Ayyuha Al-Walad dan Relevansinya dengan Pendidikan Karakter Anak - Karlina, Reni; Wahyudi, Hakmi; Rambe, Pangadilan; Hakim, Sri Wahyuni; Hidayat, Hakmi (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to explore the formation of character in Imam Al-Ghazali's Book of Ayyuha Al-Walad and its influence on the moral education of children. The emphasis on character education is intended to deter negative conduct in children by instilling moral values rooted in religious principles, law, social norms, culture, and tradition. A qualitative research approach, incorporating a literature review, was employed for this investigation, with primary focus on Imam Al-Ghazali's work